Effectiveness and cost analysis of methods used to recruit older adult sedative users to a deprescribing randomized controlled trial during the COVID-19 pandemic - Andrea L. Murphy; Justin P. Turner; Malgorzata Rajda; Kathleen G. Allen; Kamilla Pinter; David M. Gardner (Elsevier, 2023)
Background: Recruitment to clinical trials is a challenge for researchers that became more pronounced because of COVID-19 public health protective measures, especially with respect to studies enrolling older adults. We completed an effectiveness and cost analysis of the recruitment methods used in The Your Answers When Needing Sleep in New Brunswick (YAWNS NB) study, a randomized controlled trial of a deprescribing intervention that recruited older adults with chronic use of sedatives during the pandemic. Methods: Study recruitment began during the COVID-19 pandemic. Strategies included random digit dialing (RDD), a targeted mail campaign and advertising through newspapers, online platforms (Google and Facebook), and television. Other awareness raising and recruitment strategies involved seniors' organizations, pharmacies, television news stories, and referrals. Recruitment effectiveness and cost analysis involved enrollment rate (ER), cost per randomized participant (CPRP), fractional cost (FC), fractional enrollment (FE), fractional enrollment-cost ratio (FEC), and efficacy index (EI) calculations. Results: There were 1295 interested older adults with 594 randomized into the study for an enrollment rate of 46%. The efficacy index (EI) was highest for Facebook ads (EI = 0.683) followed by television (EI = 0.426), and newsprint ads (EI = 0.298). The cost of RDD was highest per randomized participant at $1117.90 and produced the lowest EI (0.013). Conclusion: Facebook ads had the best efficacy index for recruiting older adults to the YAWNS NB study during the COVID-19 pandemic and television ads produced the most enrollments. RDD was expensive and yielded few recruits. Recruitment costs can be significant for recruiting community-dwelling older adults. This experience can inform recruitment strategy and budget development for future community studies enrolling older adults, especially in the context of the COVID-19 pandemic.